Relevansi Etika Tanggung Jawab Emanuel Levinas dalam Mengatasi Persoalan Krisis Ekologi - Dominggus Bara Liwu; Hubertus Ropon Efrem Lewuk (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Ecological crisis is one of the phenomena caused by human actions that have damaged nature. These actions are influenced by the paradigm of wrong thinking about nature. There are several paradigms of thinking that affect human relations with nature such as anthropocentric, industrialistic, mechanistic and technocratic. These paradigms reveal a pattern of relationships centered on humans so that nature is only used as an object. To overcome this, humans need to build a way of thinking that is more open to the existence of nature. The author of the ethical thought of responsibility from Emanuel Levinas is relevant to construct this way of thinking. Therefore, this paper aims to review the relevance of responsibility ethics initiated by Levinas in overcoming the problem of ecological crisis.